PERP regulates enamel formation via effects on cell–cell adhesion and gene expression - Jheon, Andrew H. (Company of Biologists, 2011)
Little is known about the role of cell–cell adhesion in the development of mineralized tissues. Here we report that PERP, a tetraspan membrane protein essential for epithelial integrity, regulates enamel formation. PERP is necessary for proper cell attachment and gene expression during tooth development, and its expression is controlled by P63, a master regulator of stratified epithelial development. During enamel formation, PERP is localized to the interface between the enamel-producing ameloblasts and the stratum intermedium (SI), a layer of cells subjacent to the ameloblasts. Perp-null mice display dramatic enamel defects, which are caused, in part, by the detachment of ameloblasts from the SI. Microarray analysis comparing gene expression in teeth of wild-type and Perp-null mice identified several differentially expressed genes during enamel formation. Analysis of these genes in ameloblast-derived LS8 cells upon knockdown of PERP confirmed the role for PERP in the regulation of gene expression. Together, our data show that PERP is necessary for the integrity of the ameloblast–SI interface and that a lack of Perp causes downregulation of genes that are required for proper enamel formation.